2021
DOI: 10.1371/journal.pone.0261463
|View full text |Cite
|
Sign up to set email alerts
|

The confounding effects of eye blinking on pupillometry, and their remedy

Abstract: Pupillometry, thanks to its strong relationship with cognitive factors and recent advancements in measuring techniques, has become popular among cognitive or neural scientists as a tool for studying the physiological processes involved in mental or neural processes. Despite this growing popularity of pupillometry, the methodological understanding of pupillometry is limited, especially regarding potential factors that may threaten pupillary measurements’ validity. Eye blinking can be a factor because it frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In the 1,500 ms following the button press, there was an average modulation of 5.22% and a peak latency of 880 ms. A conspicuous trough in the pupil traces after the button press coincides with a transient but marked increase in the percentage of interpolated data. This artefact resembles the blink-induced pupillary response (e.g., Knapen et al, 2016;Yoo et al, 2021) and is therefore indicative of task-correlated blinking (i.e., participants tended to blink after button presses).…”
Section: Pupil Datamentioning
confidence: 86%
See 1 more Smart Citation
“…In the 1,500 ms following the button press, there was an average modulation of 5.22% and a peak latency of 880 ms. A conspicuous trough in the pupil traces after the button press coincides with a transient but marked increase in the percentage of interpolated data. This artefact resembles the blink-induced pupillary response (e.g., Knapen et al, 2016;Yoo et al, 2021) and is therefore indicative of task-correlated blinking (i.e., participants tended to blink after button presses).…”
Section: Pupil Datamentioning
confidence: 86%
“…This periodic pattern is redolent of van den Brink et al's (2016) pupillometry data, which were observed in a task with a similar event-related design. We attribute this to task-correlated blinking and the blink-induced pupillary response (Knapen et al, 2016;Yoo et al, 2021).…”
Section: Pupil Datamentioning
confidence: 99%
“…Similarly, stimulus location, including stimuli presented (i) in the periphery, (ii) monocularly near the nose (nasal), or (iii) achromatically in the lower visual field, evokes weaker pupil responses than other locations [127]. Blinks often induce pupil constriction and are followed by a later redilation [57,128]. Blinks can be treated as missing data or can be interpolated, the latter being more useful in context of analyses over timepoints.…”
Section: Box 3 Best Practices In Pupillometry Researchmentioning
confidence: 99%
“…Constriction also occurs after eye blinks, which are similarly accompanied by a sudden change in visual input due to the closing and opening of the eyelid. This post-eye-movement and post-blink constriction can be compensated for algorithmically during data analysis (Knapen et al, 2016; Yoo et al, 2021); however, just as for the PFE, you can never assume that pupil size is completely unaffected by eye movements and blinks.…”
Section: Experimental Designmentioning
confidence: 99%
“…This post-eye-movement and post-blink constriction can be compensated for algorithmically during data analysis (Knapen et al, 2016;Yoo et al, 2021); however, just as for the PFE, you can never assume that pupil size is completely unaffected by eye movements and blinks.…”
mentioning
confidence: 99%